Pandemia da COVID-19 e pandemia silenciosa : as expressões de hierarquia de gênero na violência intrafamiliar - Cruz, Cíntia Maria Nascimento (2023)
Historically, there is a relationship of subordination between women and men that remains sustained by the inequality built on sexual division (LERNER, 2019). A cultural construction of difference between men and women that, over the centuries, has been reproduced by the patriarchal system that imposes on women a subordinate condition of financial, emotional, and social dependence, making men's violence against women an instrument for maintaining this relationship of superiority. This research has the general objective of investigating domestic violence against women as an expression of gender hierarchy in the context of the COVID-19 Pandemic, in order to subsidize new studies and actions to protect women. This is a qualitative and quantitative research supported by the dialectic materialist-historical method, which used as instruments semi-structured interviews and focus groups. The sample included five women assisted by the Center for Women's Reference - Rompendo Paradigmas and six workers of the Network for Confronting Violence Against Women in the city of Caxias do Sul. The content analysis was based on Roque Moraes (1999), which is a research methodology used to describe and interpret the content. The guidelines recommended by CONEP-MS were followed. Situations of violence have always been part of women's daily lives. Every day it is possible to read about cases of violence in the news, newspapers, and even in social networks, which makes it visible, but does not eliminate it. With the social isolation imposed as a preventive measure against COVID-19 it was observed that domestic and intrafamily violence was potentiated and with worrying indicators. The workers of the Network of Confrontation Against Violence Against Women informed that during the pandemic, more precisely the social isolation, triggered a significant increase in the attendance in the network. The final considerations reveal that, in order to understand the permanence of women in this cycle and the critical route they take to get rid of violence, it is necessary to view this whole situation with eyes focused on a macho and patriarchal culture that legitimizes male domination over women, and also to understand the gender issue as something socially constructed. Thus, breaking the cycle in which the woman is in is not easy, so it is necessary to have a welcoming look and understand that it is possible that she breaks and returns to the cycle several times. In this context, it is up to the network professionals to welcome, listen, and support whenever this occurs, without judging her for this return, welcoming and understanding her ambiguity. It is essential that the Network of Assistance to Women in Situations of Violence act effectively in order to consolidate the implementation of a policy of confrontation to violence against women. It is necessary, therefore, to reach a standardization of guidelines and procedures for the operation of the service.